Implementation of Virtual Assistants based on Generative Artificial Intelligence created in the EDU-INNOVA Laboratory to improve the Teaching of Teachers - López Tineo, Nataly Katherine Virginia (2025)
This exploratory study investigates the implementation of four virtual assistants designed to enhance the teaching management of university professors without compromising educational quality or student engagement. A mixed-methods approach, descriptive-exploratory in nature, was adopted using a non-experimental cross-sectional design. The study population consisted of full-time faculty members from the Department of Basic Courses who achieved the highest scores in their teaching performance evaluations. The Minimum Viable Product (MVP) sample included nine of these Universidad Científica del Sur’s faculty members, impacting a total of 1060 students. The results indicate significant improvements in optimizing faculty time and the quality of educational activities provided, demonstrating the potential of ChatGPT-based virtual assistants to optimize teaching management in higher education.